Exploration and Practice of Narrative Moral Education in Primary Schools - Yang, Suhuan (Journal of Theory and Practice of Social Science, 2024)
In combination with the key experimental project of Guangdong Province "Research on Narrative Moral Education Model in Primary Schools" carried out by the school, this paper carries out theoretical discussion according to the application principles of narrative moral education, analyzes the meaning of narrative moral education, determines the research objectives and contents of the project, formulates research approaches, proves the necessity and importance of narrative moral education research through practice, and also raises the understanding of research on narrative moral education.